Novel strategy of skill lab training for parenteral injection techniques: a promising opportunity for medical students - James, Jerin; Rani, R. Jamuna (International Journal of Basic & Clinical Pharmacology, 2022)
Background: To set up an experimental pharmacology skill lab to facilitate training of specific modules for development of core competencies of parenteral drug administration and intravenous drip settings using mannequins for development of skills in administering injections for undergraduate medical students, which will be assessed using Objective Structured Practical Examination. Methods: High quality mannequins were procured from reputed companies in coordination with the biomedical engineering department of the tertiary care teaching institution. Sufficient number of multi-venous access arms, buttock injection model and models for subcutaneous and intradermal injections were obtained to facilitate individual training of 150 students in small groups during practical classes according to the checklist for the procedure. Ethical committee approval was deemed unnecessary for this study as it was a part of curriculum development. Results: Students practiced the technique confidently, without the fear doing it in a patient. This gave them the opportunity to practice in a real human surface texture, which gave them better understanding about the depth and extent of insertion of devices. Moreover, they could easily follow the steps in the check list which enabled them to practice as per protocol. Conclusions: Because of the hands-on training the students receive, we have seen a greater trend toward self-learning and better adherence to the injection technique protocol. Hence mannequin-based learning can be considered as very effective in acquiring procedural skills under the new medical curriculum in India. However, considering the high initial investment and further need of constant maintenance, cost effective mannequins need to be introduced and popularized.